Design and development of an online platform for peer tutorial scheme - Heng, Nadine Nyi Zheng (Nanyang Technological University, 2021)
The Covid-19 Pandemic has drastically changed the way education is conducted in Singapore. Tertiary institutions like Nanyang Technological University (NTU) were no exception. During the Circuit Breaker period, students were not allowed to go to school. Classes were brought online and conducted using Web-Conferencing technologies like Zoom. As Circuit Breaker measures gradually eased, hybrid classes were introduced to balance between the need for physical interaction and Social Distancing. Nevertheless, the need for Social Distancing remains due to precautionary reasons thus online classes and here to stay, at least for the near future.